Frequency of Complete Heart Block in Patients with Acute Inferior Wall Myocardial Infarction - Zia Ullah, Ibrar Khan, Wajid Khan, Mujeeb Alam Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Acute MI is the leading health issue globally affecting many lives. Aim: To determine the frequency of complete heart block in patients with acute inferior wall myocardial infarction. Study Design: Cross-sectional study. Methodology: All newly diagnosed inferior wall MI patients were included. Detailed history followed by detailed clinical examination was done. ECGs were done. Complete heart block was evaluated. It was considered as third degree AV block and was diagnosed when there was no AV nodal conduction and the P wave was completely dissociated from the QRS complexes. All this information was recorded on Performa. Data was analyzed using SPSS version 25. Cardiogenic shock was stratified among age and gender by applying chi square test. Results: Age as mean ± SD was 62 ± 8.04 years. Enrolled males were 59% while females were 41% in present study. Results showed that 19% patients had complete heart block while 81% were without it. Conclusion: It was concluded that frequency of complete heart block was high (19%) in patients with inferior wall MI